2015
DOI: 10.1007/s11605-014-2736-5
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic Conversion of Failed Silastic Ring Vertical Gastroplasty (SRVG) and Vertical Banded Gastroplasty (VBG) Into Biliopancreatic Diversion (BPD)

Abstract: Laparoscopic conversion of failed VBG to BPD is feasible and effective in further reducing weight in morbidly obese patients. Weight loss continues beyond the first postoperative year. However, the complication rate is much higher than in the primary procedure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…SRVG is a procedure that is open to many options to be laparoscopically revised. However, the conversion of SRVG into other techniques stands out in its difficulty and the decision regarding which method should be carried out in case of failed SRVG (due to excessive weight loss or weight regain) represents a real challenge (28,29). Some authors reported conversion to LAGB as a consequence of disruption of the staple-line and pouch dilatation accompanied by frequent vomiting (19,30).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…SRVG is a procedure that is open to many options to be laparoscopically revised. However, the conversion of SRVG into other techniques stands out in its difficulty and the decision regarding which method should be carried out in case of failed SRVG (due to excessive weight loss or weight regain) represents a real challenge (28,29). Some authors reported conversion to LAGB as a consequence of disruption of the staple-line and pouch dilatation accompanied by frequent vomiting (19,30).…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, Elazary et al (31) reported a higher rate of complications after SG as a revisional procedure compared to RYGB resulting in the decision to stop the conversion into SG and highlighting that RYGB is a safer choice. Finally, Abu-Gazala et al showed that a feasible and effective method to convert failed SRVG would be the biliopancreatic diversion (BPD) (29).…”
Section: Resultsmentioning
confidence: 99%